2009
DOI: 10.2174/138920109788488941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on Protein Aggregation

Abstract: This paper overviews solution additives that affect protein stability and aggregation during refolding, heating, and freezing processes. Solution additives are mainly grouped into two classes, i.e., protein denaturants and stabilizers. The former includes guanidine, urea, strong ionic detergents, and certain chaotropic salts; the latter includes certain amino acids, sugars, polyhydric alcohols, osmolytes, and kosmotropic salts. However, there are solution additives that are not unambiguously placed into these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(142 citation statements)
references
References 141 publications
4
131
1
1
Order By: Relevance
“…Importantly, sugars, polyols, many amino acids (other than arginine and proline), racemic mixtures of L-and D-proline, and hydroxyproline have only little or no ability to form supramolecular aggregates and to inhibit protein aggregation. These same compounds, however, are known to stabilize native structure of proteins by preferential exclusion (Paleg et al, 1981;Samuel et al, 2000;Myung et al, 2006;Das et al, 2007;Hamada et al, 2009). We observed little or no effect of D-proline and hydroxyproline on larval freeze tolerance in our experiments (Table S3), which suggests that the formation of supramolecular aggregates of proline and arginine and inhibition of aggregation of partially unfolded proteins might represent another mechanism, in addition to preferential exclusion, that explains the high freeze tolerance in D. melanogaster larvae reared on diets augmented specifically with arginine and proline.…”
Section: Binding Partially Unfolded Proteinsmentioning
confidence: 99%
“…Importantly, sugars, polyols, many amino acids (other than arginine and proline), racemic mixtures of L-and D-proline, and hydroxyproline have only little or no ability to form supramolecular aggregates and to inhibit protein aggregation. These same compounds, however, are known to stabilize native structure of proteins by preferential exclusion (Paleg et al, 1981;Samuel et al, 2000;Myung et al, 2006;Das et al, 2007;Hamada et al, 2009). We observed little or no effect of D-proline and hydroxyproline on larval freeze tolerance in our experiments (Table S3), which suggests that the formation of supramolecular aggregates of proline and arginine and inhibition of aggregation of partially unfolded proteins might represent another mechanism, in addition to preferential exclusion, that explains the high freeze tolerance in D. melanogaster larvae reared on diets augmented specifically with arginine and proline.…”
Section: Binding Partially Unfolded Proteinsmentioning
confidence: 99%
“…At high concentrations, salts exert specific effects on protein, resulting in the precipitation of these compounds. Salts act on the increase of the interfacial tension between the protein surface and the solvent, changing the solubility (Hamada et al 2009). …”
Section: Application Of Cut and Cut-n1 In The Degradation Of Plasticsmentioning
confidence: 99%
“…PEG is one of the most versatile water soluble polymers for refolding recombinant proteins and for stabilizing proteins by chemical modification (Hamada et al 2009). In this study, the Pareto chart ( Figure 5) shows the positive effect of the interaction between glycerol and PEG-200 in the activity of CUT-N1.…”
Section: Formulation Of Concentrated Metabolic Liquid With Cutinolytimentioning
confidence: 99%
“…Numerous solution additives had been proved useful for this goal. It had been reported that the non-detergent surfactants are more favourable for aggregation suppression than the detergents [36]. Therefore, we add surfactant to the growth media and observed 2.8 fold enhancements in enzyme activity when compared with production without surfactant.…”
Section: Firstmentioning
confidence: 80%